Investigation of the Wear Resistance Properties of Cr/CrN Multilayer Coatings against Sand Erosion. (5th May 2015) - Naveed, Muhammad; Obrosov, Aleksei; Weiß, Sabine
Abstract : The wear of metallic components used in gas and steam turbines due to erosive sand particles leads to a tremendous decrease in their lifetime. This wear can be reduced by the use of suitable erosion resistant coatings resulting in lower maintenance costs. In this context, multilayer Cr/CrN PVD coatings using an industrial coater were designed and applied on Inconel 718, a material which finds its application in gas turbines. A variation in the bimodal period has been induced in order to achieve an optimal coating architecture providing optimum properties needed for the erosion resistant coatings. The coating was deposited using a single Cr-target with an induction of N2 during the nitriding phase at a temperature of 480–500°C and the coating thickness of 24–26  μ m was kept constant throughout. The erosion tests were conducted at angles of 30°, 60°, and 90°. The sand used for the test is an irregular shaped SiO2 . The erosion tests were followed by a detailed microscopic examination of the eroded coating structure in combination with nanoindentation and scratch tests.